Democracy at Risk? Politics and Governance under the ANC. Issue 1 (March 2014) - Southall, Roger
The negotiated settlement of 1994 established South Africa as a constitutional democracy. Under Nelson Mandela, the new democracy basked in a glow of national reconciliation, early growth, and optimism. Subsequently, however, the national sense of collective well-being has declined. Racial inequality has narrowed, but the fundamental features of the apartheid economy remain, including a significant section of the population living in absolute poverty, despite the efforts of the government to combine economic growth with redistribution. Given the continued entrenchment of white economic power, the African National Congress (ANC) has sought to use its capture of the state to promote the empowerment of blacks. However, having assumed the characteristics of a "dominant party" assured of successive election victories, the ANC now presides over a party-state whose accountability leaves much to be desired, providing opportunity and scope for corrupt and predatory behavior by significant elements of the party's elite. Further merging of party and state challenges constitutionalism and threatens the rule of law. It is only when the ANC's electoral hegemony is eroded that we will discover whether, if faced by loss of power, it will obey or disregard its democratic heritage.